Pengaruh Tingkat Suku Bunga, Jumlah Nasabah, dan Kredit Gadai yang Disalurkan terhadap Laba Bersih Perum Pegadaian Cabang Ambon - Borolla, Johanis Darwin (PRESTASI, 2013)
This study aimed to examine the effect of the interest rate, number of customers, and mortgage loans are disbursed to net income Pawnshop Branch Ambon. By using secondary data from the years 2008-2012, this study was able to prove that the interest rate is positive but not significant effect on corporate profitability, as shown by the t value of 1.075; Customer Numbers positive and significant effect of the increase in profits derived Pawnshop Branch Ambon, this is indicated with a t value of 3.114; mortgage loans which connected positive and significant effect of the increase in profits derived pawnshop Branch Ambon, as shown by the t value of 2.059. R-square value in this research model is 0.771 with adjusted R-squared of 0.742. The R-square value indicates that inndependen variables in this study were able to explain 77.1% of the dependent variable. This means that there is 22.9% of other factors that influence profit Pawnshop Branch Ambon.Keywords : Interest Rates, Mortgage Loans, Number of Clients, Profit.